A democracia confiscada : a constituição do inconsciente neoliberal no discurso do sujeito midiático Veja (1985-1994) - Rossatti, João Paulo (2022)
What is a subject? What is a communication vehicle? Is it possible to methodologically approach a journalistic communication vehicle in the same way as psychoanalysis approaches a subject? If it is even possible to read it as a subject, does it have any ideology? How should we understand the concept of ideology and what is its importance for the subjective constitution? Does Veja magazine have an ideology? If so, is it neoliberal or what? When did Brazil become neoliberal? It was with these questions in mind that I initially approached my object, Veja magazine. To extract an answer – as I hope to make clear throughout the text – I divided this thesis into three parts. In the first, I develop the methodological development of the concept of media subject, it is he who serves me as a support to analyze Veja magazine, and from it, I indicate that, especially for printed communication vehicles, it is possible to understand how media subjects not only have an ideology, as it operates at the level of ontology, that is, identification with the fundamental fantasy of ideological discourse is essential for the very existence of the subject; In this first part, I also show how this ideological ontology needs, during the process of subjectivation of the media subject, to be repressed, thus transmuting into deontology of journalistic work whose result is the ability to “educate the senses” of readers. In the second part of the text, I try to identify how ideology, from the žižekian definition of the concept, should not be understood as a veil that prevents us from accessing the “true” reality but operates as the necessary mediation to have access to this reality. same reality; With this in mind, I move on to the second moment of this part's argument, that is, how neoliberal ideology has become entrenched as a structuring fantasy of reality these days. After building this methodological and analytical basis, I finally come to the third part, in which I analyze how the magazine Veja, our subject under analysis, between the beginning of the New Republic, in March 1985, and the presidential election of 1994 (this one under the neoliberal sign of the Plano Real), became one of the radiators of the ideological discourse based on the neoliberal unconscious. Friedman, Israel Kirzner) to demonstrate how these ideas were already there (!) and that their constant repetition (not only in Veja) was essential for the dissemination and incorporation of the ideological fantasy in its neoliberal facet that resulted in the confiscation of the own idea of what democracy is (defined here as Hayekian democracy). I end the text with a conclusion that opens more questions than ends the thesis, after all, is it possible for Hayekian democracy (based on the postulates of neoliberalism) not to produce a social bond whose fundamental affection is hatred? And doesn't this mean, then, the very Brazilianization of the world? I still don't know the answer, I can only say that every time “the future imposes itself” the “past cannot hold”.